SPHERE AND OBJECT OF ADMINISTRATIVE AND LEGAL SUPPORT FOR THE IMPLEMENTATION OF THE STATE LAW ENFORCEMENT FUNCTION IN AVIATION - Пивовар, Юрій Ігорович; Сторощук, Ольга Ігорівна; Дирієнко, Олександр Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: determination of the sphere and object of administrative and legal support for the implementation of the state law enforcement function in aviation. Research methods: cross-sectoral approach, which applied the historical and legal method, which made it possible to study the retrospective development of the concept of «aviation», «aviation activity»; methods of analysis and synthesis helped to determine the essence of the object of administrative and legal support for the implementation of state law enforcement functions in aviation. Results: the concept of general aviation has been defined - a type of civil aviation that is not associated with both the commercial operation of air transport and the specialized non-commercial operation of air transport while providing specialized types of activities (agriculture, construction, photography, geodesy, surveillance and patrolling, air advertising, etc. etc.). The aviation industry of Ukraine is a component of the transport system for the production (including, development, testing, manufacturing, maintenance, repair and disposal) of aircraft, their use in airspace, as well as air traffic management activities (including airspace management), air traffic services and air traffic flow management) of Ukraine. It was proposed to consolidate the formulated definition in a legislative act, in particular, Article 1 of the Air Code of Ukraine. Discussion: the object of administrative and legal support for the implementation of the state law enforcement function in aviation is proposed to be interpreted in a broad and narrow sense. In a broad sense, this is an aviation activity; narrowly - activities for the development, experimental testing, manufacturing of aircraft with their release into circulation, operation, maintenance and disposal, as well as activities for air traffic maintenance, management of the use of the airspace of Ukraine and the organization of air traffic flows.